CSIS13 - Project Management in Information Technology February 1999 - PPSKOM, Pusat Pengajian Sains Komputer (Universiti Sains Malaysia, 1999)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 1998/99 February 1999 CSIS13 - Project Management in Information Technology Duration: [3 hours] INSTRUCTION TO CANDIDATE: • Please ensure that this examination paper contains FIVE questions in FOUR printed pages before you start the examination. • Answer ALL from questions 1 to 4 and choose any THREE from question 5. • You can choose to answer either in Bahasa Malaysia or English.